Tradisi Minjung Di Desa Tanjung Pura Dalam Perspektif Hukum Adat dan Hukum Islam - Alfarisi, Sulthan Arfan; Zailia, Siti; Isa, Legawan (Muqaranah, 2023)
The "minjung" tradition is one of the beliefs of the people of Tanjung Pura village, Pengandonan subdistrict, Ogan Komering Ulu (OKU) district. Meanwhile, according to the term "minjung" tradition is serving food out of gratitude for achieving the goal and praying for the spirits of deceased ancestors. The community usually carries out this minjung tradition, namely after the rice harvest, before weddings and before Eid al-Fitr. Then, to examine the research, we carried out investigations through field observations and interviews with several sources. From this research it can be concluded that the procedures for implementing the minjung tradition are providing dishes in the form of food before carrying out the tradition, reading Surah al-Fatihah, continuing to read Surah Al-Ikhlas, Surah Al-falaq, Surah An-Nas, Surah Al-Baqarah 1-5, And continued praying. According to Customary Law, the implementation of this tradition must be carried out because people believe that if it is not implemented, undesirable things will happen, whereas according to Islamic Law, if the food served is used as an offering to the spirits of ancestors/ancestors, then it is Urf fasid, that is, it is not permitted by law. It is Haram, and if the food is served as a form of gratitude to Allah for what has been achieved and so that the future will be even better, then Urf Sahih applies, that is, it is permissible, then the law is Sunnah.